Estratégia rede cegonha: uma análise da humanização da assistência à gestante e o enfrentamento da violência obstétrica no município de Santarém/PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
This research has the main objetive to analyze the assistance to pregnant women in the context of the public policy “Strategy Rede Cegonha” in the city of Santarém/PA. Currently, society has been concerned with conducting studies and debates about care for pregnant women and their babies in view of the dissemination of information about obstetric violence, as well as concepts related to humanized childbirth. therefore, this study, in view of society's evident search for information, aims to investigate to what extent the implementation of the stork network strategy in Santarém/PA provides for the humanization of care for pregnant women and the confrontation of obstetric violence. Thus, the humanization of care for pregnant women is the object of analysis. It’s intended to analyze whether the absence of specialized centers for the care of pregnant women and their babies in the municipality of Santarém configures an element that enhances the occurrence of obstetric violence, if the body of professionals working in the area of care during delivery and birth is based on a classic model oriented by the practice of medicalization of childbirth, hindering the use of humanized care for pregnant women and coping with obstetric violence, as well as whether the implementation of Rede Cegonha in Santarém/PA provides humanization of care for pregnant women and coping with obstetric violence. Therefore, this scientific analysis aims to analyze the structure of the Rede Cegonha in the municipality of Santarém/PA, verify what is the stage of implementation/implementation and identify if there’re challenges for its implementation. As a research methodology applied for the scientific investigation in question, bibliographic review, data collection from public agencies will be used, as well as a semi-structured interview with professionals working in care for pregnant women in the city of Santarém/PA with focus in the public service network held at the Municipal Hospital. By conducting the research, it is concluded that the Rede Cegonha strategy is not consolidated in all aspects provided for in its institution ordinance No. 1459/2011, however the current structure to some extent contributes to humanized care and combating obstetric violence.
Keywords: Políticas Públicas; Rede Cegonha; Assistência à gestante; violência obstétrica; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS